S127 Are girls always thinner than boys? using uk cystic fibrosis (cf) registry data (2008–2013) to examine weight changes between the sexes from childhood and beyond. (15th November 2017) - Hippolyte, SS; Simmonds, NJ; Bilton, D; Griesenbach, U; Keogh, R
Abstract : Introduction: Worse BMI in CF is associated with worse survival. The UK-CF Registry was used to examine weight differences between sexes, and determine the age this occurs, and how this relates to feeding supplementation (FS) and outcomes, such as change in FEV1, intravenous antibiotic use (IVABx) and mortality. Methods: Cross-sectional analysis (2013) of weight variables (expressed as BMI for subjects≥16 years, BMI percentiles (BMIP) individuals<16 years and BMI Z-scores for 6–23 year-old subjects), FS and IVABx were compared between sexes using paired t-tests and chi-squared analyses. Age groups were created to examine adolescence in detail (0–5, 6–12, 13–15, 16–19, 20–23, 24–29 and ≥ 30 years). A longitudinal analysis (2008–2013) of weight change investigated potential explanatory variables between the sexes, such as diabetic status (CFRD) and FS. Results: Cross-sectional Boys 13–15 years had lower mean BMIP than girls (41.2 vs 50.5 p<0.001). Boys had a lower Z-score than girls for age 13–23 years. Mean BMI was significantly lower in females (21.9 vs 22.5 p<0.001). More females were underweight (BMI <19) than males (18.9% vs 14.0% p<0.001), this was specifically observed in ages≥24 years. Underweight individuals died younger than individuals with BMI ≥ 19 (29.3 years vs 36.0 years p=0.007). Lower weight was associated with more IVAbx days. Males had higher rates of FS (34.7% vs 28.9% in females p<0.001) specifically when≥16 years. These sex differences were not explained by differences in ethnicity, genotype or socio-economic status. Longitudinal: Boys had a greater fall in BMIP (8.3 vs 4.1 in females p=0.002). In adulthood, females had significantly less increase in BMI (0.20 vs 0.57 in males p<0.001). FEV1 decline was greater in females (7.4% vs 5.9% in males p=0.0016) not receiving FS, with no difference in change in FEV1 between the sexes in those receiving FS. Conclusion: From ≥ 16 years boys changed from having lower BMIP to higher mean BMI and lower rates of underweight status in adulthood. Higher rates of FS in adolescent boys might explain this. Lower weight is associated with earlier death and increased IVABx use. In individuals without FS females have a greater decline in FEV1 than males, this is not seen in individuals on FS. This has not been previously shown and warrants further analysis.